2007
DOI: 10.1677/joe-07-0267
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-23 regulates parathyroid hormone and 1α-hydroxylase expression in cultured bovine parathyroid cells

Abstract: Fibroblast growth factor-23 (FGF23) is a circulating factor that decreases serum levels of inorganic phosphate (Pi) as well as 1,25-dihydroxyvitamin D 3 . Recent studies also suggest a correlation between serum levels of FGF23 and parathyroid hormone (PTH) in patients with chronic kidney disease. It is, however, unknown whether FGF23 directly modulates PTH expression, or whether the correlation is secondary to abnormalities in Pi and vitamin D metabolism. The objective of the current study was therefore to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
269
3
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(291 citation statements)
references
References 40 publications
10
269
3
9
Order By: Relevance
“…Furthermore, it is of interest that this patient's hyperparathyroidism occurs in the presence of hypophosphatemia and not the elevated phosphate levels that accompany renal failure. Moreover, ␣-Klotho has been reported to mediate PTH secretion in vitro through its maintenance of cell surface Na ϩ /K ϩ -ATPase activity (22); conversely, FGF23 has recently been shown to inhibit expression of PTH mRNA and secretion of PTH from parathyroid cells (35). Whether the elevated FGF23 level seen in our patient is the direct result of increased ␣-Klotho (for example, if degradation of FGF23 were prevented by interaction with ␣-Klotho) or is part of a negativefeedback loop responding to hyperparathyroidism is difficult to discern at present.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is of interest that this patient's hyperparathyroidism occurs in the presence of hypophosphatemia and not the elevated phosphate levels that accompany renal failure. Moreover, ␣-Klotho has been reported to mediate PTH secretion in vitro through its maintenance of cell surface Na ϩ /K ϩ -ATPase activity (22); conversely, FGF23 has recently been shown to inhibit expression of PTH mRNA and secretion of PTH from parathyroid cells (35). Whether the elevated FGF23 level seen in our patient is the direct result of increased ␣-Klotho (for example, if degradation of FGF23 were prevented by interaction with ␣-Klotho) or is part of a negativefeedback loop responding to hyperparathyroidism is difficult to discern at present.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in PTH found in Ksp-KL 2/2 mice could could either be caused by higher systemic calcium levels or the fact that FGF23 inhibits PTH synthesis and secretion by directly targeting the parathyroid glands. 23,24 In contrast, Ksp-KL 2/2 mice challenged with a high-phosphate diet had higher PTH than wild-type littermates. The underlying mechanisms remain unclear.…”
Section: /2mentioning
confidence: 94%
“…[1][2][3][4] Parathyroid cells also possess FGFR-klotho receptors, and experimental studies have shown that FGF23 inhibits parathyroid hormone (PTH) production and secretion. [5][6][7] However, in uremic animals, hyperplastic parathyroid glands fail to respond to FGF23 because the expression of FGFR-klotho is downregulated. [7][8][9][10][11] FGF23 effectively increases the output and decreases the input of phosphorus because it directly increases phosphaturia and indirectly decreases intestinal phosphorus absorption by decreasing calcitriol values.…”
mentioning
confidence: 99%